pH-Dependent single-step rapid synthesis of cuo and cu2o nanoparticles from the same precursor - Nikam, Arun V.; Arulkashmir, Arulraj; Krishnamoorthy, Kothandam; Kulkarni, Amol A.; Bhagavatula L. V. Prasad (Crystal Growth & Design, 2014)
A single-step protocol to prepare Cu2O and CuO nanocrystalline particles from the same precursor by microwave irradiation has been developed using the pH of the solution as the only variable parameter. The utility of different bivalent Cu-precursors for synthesis of CuO and Cu2O nanoparticles was also investigated. The morphology, phase purity, and optical properties of these nanoparticles were analyzed using TEM, SEM, XRD, and optical spectroscopy. The band edges were determined using cyclic voltammetry. Field effect transistors based on CuO nanoparticles showed a hole mobility of 3.5 x 10(-2) cm(2) V-1 s(-1), making them a suitable candidate for energy-related applications. The effect of hydrazine vapor exposure on the IV-characteristics of CuO nanoparticles was also investigated. This revealed a decrease in source current with respect to time.

Microwave assisted batch and continuous flow synthesis of palladium supported on magnetic nickel nanocrystals and their evaluation as reusable catalyst - Nikam, Arun V.; Kulkarni, Amol A.; Prasad, Bhagavatula L. V. (Crystal Growth & Design, 2017)
Palladium nanocrystals (NCs) supported on nickel NCs (Pd/Ni) were synthesized in a continuous flow manner by the microwave-assisted method in the presence and absence of oleylamine. Parameters optimized for batch experiments were considered while performing continuous flow synthesis. The Pd/Ni NCs synthesized in the presence of oleylamine displayed good catalytic activity for hydrogenation of aromatic nitro compounds, and those bearing alkene, and alkyne moieties. The ferromagnetic character of the supporting nickel NCs allowed the recovery of the catalyst and these recovered catalysts could be reused several times.

Scalable microwave-assisted continuous flow synthesis of CuO nanoparticles and their thermal conductivity applications as nanofluids - Nikam, Arun V.; Dadwal, Arun H. (Advanced Powder Technology, 2019)
We have demonstrated the novel and scalable synthesis of CuO nanoparticles by an integration of microwave and flow synthesis. The shape and size of CuO nanoparticles were tuned by changing the concentration of copper precursor. The production rate of CuO nanoparticles was found to be 5 g/h with 70% conversion of copper acetate into the CuO nanoparticles. The thermal conductivity of CuO nanofluid prepared in ethylene glycol showed linear enhancement with increase in the volume content of CuO nanoparticles produced in batch and flow reactors. (C) 2018 The Society of Powder Technology Japan. Published by Elsevier B.V. and The Society of Powder Technology Japan. All rights reserved.
Keywords: Flow synthesis; Microwave; Nanofluids; Nanoparticles; scale-up; Thermal conductivity

Antisolvent based ultrasound-assisted batch and continuous flow precipitation of metformin hydrochloride particles - Pal, Sayan; Nikam, Arun V.; Kulkarni, Amol A. (Journal of Flow Chemistry, 2021)
Small sized particles of the antidiabetic drug metformin hydrochloride (MET.HCl) were produced by antisolvent based precipitation using an ultrasound assisted inverted jet reactor (IJR). This novel approach was implemented as a small passive mixer in which intensified turbulent mixing of the solution and the antisolvent occurred under controlled conditions. The optimized conditions for antisolvent precipitation (ASP) were investigated by studying the effect of solute concentration, antisolvent to solvent ratio and antisolvent temperature in batch systems. The optimized batch precipitation conditions were successfully translated into continuous flow process for the ultrasound assisted inverted jet reactor. The ability of the proposed clogging free inverted jet reactor approach can provide a scaled up alternative pathway to micro and millifluidic devices for manufacturing of small sized API particles, such as, MET.HCl for the formulations and encapsulations on an industrial scale.
Keywords: Continuous antisolvent precipitation; Jet-reactor; Metformin; supersaturation; Ultrasound